2006
DOI: 10.1002/ch.35
|View full text |Cite
|
Sign up to set email alerts
|

Frontal functions, connectivity and neural efficiency underpinning hypnosis and hypnotic susceptibility

Abstract: An update is provided of an earlier review (Gruzelier, 1998) of the range of evidence for neurophysiological changes in frontal and lateralized functions with hypnosis, changes which have differentiated high from low hypnotically susceptible subjects, and which led to a working model and neuropsychological translation of the hypnotic induction process. New evidence is outlined from an fMRI/EEG study. This study also disclosed the importance of neural efficiency in left lateral frontal and anterior cingulate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 73 publications
(87 reference statements)
7
57
1
1
Order By: Relevance
“…Theories of hypnosis frequently highlight the top-down view and tend to emphasize the roles of cognitive control and executive (or metacognitive) monitoring functions based in prefrontal and anterior cingulate cortices and broader frontal-parietal networks (Dienes & Perner, 2007;Egner & Raz, 2007;Gruzelier, 2006;Jamieson & Woody, 2007;Lynn, Kirsch, & Hallquist, 2008;Woody & Sadler, 2008).…”
Section: Hypnosis As Top-down Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Theories of hypnosis frequently highlight the top-down view and tend to emphasize the roles of cognitive control and executive (or metacognitive) monitoring functions based in prefrontal and anterior cingulate cortices and broader frontal-parietal networks (Dienes & Perner, 2007;Egner & Raz, 2007;Gruzelier, 2006;Jamieson & Woody, 2007;Lynn, Kirsch, & Hallquist, 2008;Woody & Sadler, 2008).…”
Section: Hypnosis As Top-down Regulationmentioning
confidence: 99%
“…Owing to its role in monitoring and cognitive control (Fleming, Ryu, Golfinos, & Blackmon, 2014;Miller & Cohen, 2001), multiple theories of hypnosis have hypothesized a role for atypical prefrontal functioning in high hypnotic suggestibility (Dienes & Hutton, 2013;Gruzelier, 2006;Woody & Bowers, 1994). Multiple well-powered behavioural studies have suggested that highly suggestible individuals exhibit impaired performance on cognitive tasks known to depend on prefrontal cortex, such as selective attention and working memory (Farvolden & Woody, 2004;Jamieson & Sheehan, 2004;Khodaverdi-Khani & Laurence, 2016;Terhune et al, 2011c).…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitymentioning
confidence: 99%
“…Whilst some researchers have argued for a differential role for the cerebral hemispheres in producing the hypnotic experience (e.g. Gruzelier, 2006), an equally fruitful approach might be investigating functions associated with superior medial regions (BA6,8,& 9) and contrasting those with functions associated with inferior lateral regions (BA44, 45, and 46) of the PFC (see also e.g. Kallio, Revonsuo, Hämäläinen,…”
Section: Neuroimaging Evidence Reveals Both Increased and Decreased Fmentioning
confidence: 99%
“…see Parris, Dienes & Frontal Executive Functions in Hypnosis and Hypnotic Suggestibility 16 Hodgson, 2012). This would reduce oxygenation requirements and therefore the resulting fMRI signal (Gruzelier, 2006) making it more difficult to identify the neural loci of such processes via neuroimaging. Further work is needed to identify the neural correlates of control following post-hypnotic suggestions given their potential to elucidate the contribution of FEFs to the production of suggestions.…”
Section: Neural Correlates Of Post-hypnotic Suggestionsmentioning
confidence: 99%
“…This theory has received support from studies demonstrating that hypnosis reduces the connectivity between frontal lobe and other brain areas, most importantly disconnecting frontal lobe from the anterior cingular cortex, a brain structure usually associated with conflict 5 monitoring (Egner, Jamieson, & Gruzelier, 2005;Fingelkurts, Kallio, & Revonsuo, 2007;Gruzelier, 2006). Therefore, hypnosis may serve as an appropriate tool to investigate the role of executive frontal system in performing a PM task.…”
Section: Introductionmentioning
confidence: 99%